The role of libraries in lifelong learning: the case of public libraries in Istria - Fabris, Martina (2010)
The aim of the research is to show the quality of lifelong learning programs for public library users in Istria. Public libraries were founded and continue to serve as premier institutions for lifelong learning. According to the European Commission, lifelong learning "promotes the development of knowledge and competences that will enable each citizen to adapt to the knowledge-based society and actively participate in all spheres of social and economic life, taking more control of his or her future." Lifelong learning is defined as "the whole cycle of learning from childhood learning, formal education at all levels through to independent learning throughout adult life, including distance learning, whether or not credits, certificates or diplomas are involved". Lifelong learning is necessary to meet the demands of today's fast-paces, ever-changing workplace requiring an increasing amount of knowledge, and public libraries serve as nodes that connect the local learning setting with the global resource of information and knowledge, so that they play a role of fundamental importance in the development of future systems of lifelong learning. Methods like questionnaire and interviews will be used in the research. This paper should for the first time give a comprehensive insight into the lifelong learning programs for public library users in Istria. The results should point how lifelong learning programs may develop in the future, according to the needs of the society and labour market and what role public libraries will have in it.